ИЗМЕНЕНИЕ РЕЛАКСАЦИОННЫХ ПРОЦЕССОВ С ВОЗДЕЙСТВИЕМ РАДИАЦИИ В КВАНТОВО-РАЗМЕРНЫХ СТРУКТУРАХ - Шарибаев, М.Б.; Жалелов, М.А.; Камалов, А.Б.; Низаматдинова, Г.Б.; Байрамов, О.Д. (SCIENCE and SOCIETY, 2022)
For quantum A2V6, the degradation of photoluminescence Phl takes place at significantly smaller doses of irradiation. On the shear of the energy shift of photoluminescence of Phl, a change in the profile of the pits as a result of irradiation is calculated. The role of diffusion is determined of Cd and internal stresses in the radiation-stimulated degradation of quantum-dimensional structures.